KEPEMIMPINAN KEPALA SEKOLAH DI SEKOLAH PENGGERAK DAN SEKOLAH BUKAN SEKOLAH PENGGERAK DALAM IMPLEMENTASI KURIKULUM MERDEKA - Prabowo, Kusdiyanto Eko; Harjito, Harjito; Rasiman, Rasiman (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the leadership of school principals in Mobilizing Schools and non-Mobilizing Schools in the implementation of Merdeka Curriculum in Central Semarang District, Semarang City. Participants consisted of school principals, classroom teachers, subject area teachers, school administration staff, school supervisors, and parents. Data collection techniques using observation, interviews, and documentation. The data validity of this research used Source triangulation technique and member checking. Data analysis techniques that can be taken are thematic analysis or coding in the context of phenomenology including: Organizing Data, Coding Data, Identifying Major Themes and drawing conclusions. The results showed that the principal's transformational leadership plays an important role in the effective implementation of the Merdeka Curriculum. In contrast, Non-Mover Schools still face challenges in implementing transformational leadership. Principals in these schools tend to focus more on administrative aspects than encouraging learning innovation. This results in teachers receiving less guidance in implementing the Merdeka Curriculum, and limited facilities further hinder the implementation of innovation. The implications of this study emphasize the importance of transformational leadership training for principals, especially in schools that have not yet become Mover Schools.